Written distractor words influence brain activity during overt picture naming - Diaz, Michele T.; Hogstrom, Larson J.; Zhuang, Jie; Voyvodic, James T.; Johnson, Micah A.; Camblin, C.Christine (Frontiers in Human Neuroscience, 2014)
Language production requires multiple stages of processing (e.g., semantic retrieval, lexical selection), each of which may involve distinct brain regions. Distractor words can be combined with picture naming to examine factors that influence language production. Phonologically-related distractors have been found to speed picture naming (facilitation), while slower response times and decreased accuracy (interference) generally occur when a distractor is categorically related to the target image. However, other types of semantically-related distractors have been reported to produce a facilitative effect (e.g., associative, part-whole). The different pattern of results for different types of semantically-related distractors raises the question about how the nature of the semantic relation influences the effect of the distractor. To explore the nature of these semantic effects further, we used functional MRI to examine the influence of four types of written distractors on brain activation during overt picture naming. Distractors began with the same sound, were categorically-related, part of the object to be named, or were unrelated to the picture. Phonologically-related trials elicited greater activation than both semantic conditions in left insula and bilateral parietal cortex, regions that have been attributed to phonological aspects of production and encoding, respectively. Semantic conditions elicited greater activation than phonological trials in a left posterior MTG, a region that has been linked to concept retrieval and semantic integration. Overall, the two semantic conditions (categorically-related and part-whole) did not differ substantially in their functional activation which suggests a similarity in the semantic demands and lexical competition across these two conditions.